Studi Komparatif Kompetensi Dasar K- KMA 183 dan KMA 164 pada Mata Pelajaran Bahasa Arab Kelas VII MTs pada Kompetensi Ranah Kognitif - Adam, Muhammad Zikran; Muhammad Jundi; Ali, Ibadurrahman; Laubaha, Siti Aliyya; Kadir, Suleman (Assuthur: Jurnal Pendidikan Bahasa Arab, 2023)
The Ministry of Religion has issued a decision in 2019 for curriculum changes in PAI and Arabic subjects to replace the previous KMA decision, namely KMA 164 and now replaced with KMA 183 & 184. With this new thing, some differences will also be found. This research aims to describe the differences and similarities that exist in specific competencies in cognitive shutter as well as the advantages and disadvantages that exist in Arabic subjects. This study used a literature study approach by means of literature and the object of research was the Arabic language curriculum in class VII Tsanawiyyah. It was found that there are several differences and similarities in terms of objectives and materials that must be mastered by students. Therefore, the teacher must adjust more and be more competent in teaching learning.